CIn Problems 59–70, find each indefinite integral and check the result by differentiating.
68.
∫
e
x
2
e
x
−
1
d
x
With differentiation, one of the major concepts of calculus. Integration involves the calculation of an integral, which is useful to find many quantities such as areas, volumes, and displacement.
9.
Needing a break from studying, you take a walk to the Pogonip koi pond, whereupon
a wild-eyed stranger pops out from behind a redwood tree and directs the following polemic
in your general direction: "The lies those so-called teachers at that university promulgate, let
me tell you. I know the truth that they don't want you to know. As plain as day, " = 0
for all n ≥0. It's an easy induction proof, see?" He hands you a leaflet, where you see the
proof that they don't want you to see:
We proceed by strong induction on n.
Base case: n = 0. We have 10:
Induction step: Assume that
d1 =
=
= 0.
dx
dxk
dx
= 0 for all kn. Then, by the product rule,
nd
dx
da
1x+1 = 1/1(x²x²) = x²±²x² + x 11 x²
d
=
x.0+x¹.0 0.
dx
This completes the induction.
That derivative rule doesn't seem like the one you learned, but there's nothing obviously
wrong with the proof. Is he right, are the math professors propping up the interests of Big
Calculus? Or should he have paid better attention in CSE 16? What's going…
Apply Euler's method on the next differential equation with the initial initial value and in the given interval. You must include: a) table and b) graph.\\\[\frac{d y}{d x}=y^{2}-4 x, \quad y(0)=0.5 ; \quad 0 \leq x \leq 2, \quad \Delta x=0.25\]
7.
Define the sequence {b} by
bo = 0
Ել ։
= 2
8.
bn=4bn-1-4bn-2 for n ≥ 2
(a) Give the first five terms of this sequence.
(b) Prove: For all n = N, bn = 2nn.
Let a Rsuch that a 1, and let nЄ N. We're going to derive a formula for
Σoa without needing to prove it by induction. Tip: it can be helpful to use C1+C2+...+Cn
notation instead of summation notation when working this out on scratch paper.
(a) Take a a² and manipulate it until it is in the form Σ.a.
i=0
(b) Using this, calculate the difference between a Σ0 a² and Σ0 a², simplifying away the
summation notation.
i=0
(c) Now that you know what (a – 1) Σ0 a² equals, divide both sides by a − 1 to derive the
formula for
a².
(d) (Optional, just for induction practice) Prove this formula using induction.
Chapter 5 Solutions
Pearson eText for Calculus for Business, Economics, Life Sciences, and Social Sciences, Brief Version -- Instant Access (Pearson+)
Need a deep-dive on the concept behind this application? Look no further. Learn more about this topic, subject and related others by exploring similar questions and additional content below.